2007
DOI: 10.1111/j.1365-313x.2006.03012.x
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminus of pokeweed antiviral protein has distinct roles in transport to the cytosol, ribosome depurination and cytotoxicity

Abstract: SummaryPokeweed antiviral protein (PAP) produced by pokeweed plants is a single-chain (type I) ribosome-inactivating protein (RIP) that depurinates ribosomes at the a-sarcin/ricin loop of the large rRNA, resulting in inhibition of translation. Unlike the type II RIPs, which have an active and a binding moiety, PAP has only the active moiety. The mechanism by which toxins without a binding moiety gain access to cytosolic ribosomes is not known. We set up yeast as a simple and genetically tractable system to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Most RIPs specifically recognize galactosyl terminated glycoproteins on the cell surface and as such facilitate the entry of the A-chain into the cell where it can exert its enzymatic activity on ribosomes or other cellular structures. Recently Baykal and Tumer (2007) have demonstrated that a conserved sequence at the C-terminus of the pokeweed antiviral protein (type-1 RIP) mediates its transport to the cytosol suggesting that type-1 and type-2 RIPs may use a common signal to enter the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…Most RIPs specifically recognize galactosyl terminated glycoproteins on the cell surface and as such facilitate the entry of the A-chain into the cell where it can exert its enzymatic activity on ribosomes or other cellular structures. Recently Baykal and Tumer (2007) have demonstrated that a conserved sequence at the C-terminus of the pokeweed antiviral protein (type-1 RIP) mediates its transport to the cytosol suggesting that type-1 and type-2 RIPs may use a common signal to enter the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…It is less clear how the type I RIPs achieve cytosolic translocation, though there are reports of the C-terminus of PAP being necessary for cytosolic translocation and toxicity [76], when studied using a yeast expression system [76]. Here, the propensity of various PAP truncations and point mutation were examined in relation to PAP's ability to navigate ER exit and depurinate ribosomes [76]. What is not clear is how a type I RIP exits the endocytic system that by default would deliver the protein to the endolysosome and destruction.…”
Section: Accessing the Cytosol Via The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…CT, PEA, ST and PT have all been reported to translocate via the Golgi and ER en route to the cytosol, utilising a variety of retrograde transport strategies. It is less clear how the type I RIPs achieve cytosolic translocation, though there are reports of the C-terminus of PAP being necessary for cytosolic translocation and toxicity [76], when studied using a yeast expression system [76]. Here, the propensity of various PAP truncations and point mutation were examined in relation to PAP's ability to navigate ER exit and depurinate ribosomes [76].…”
Section: Accessing the Cytosol Via The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the depurination fragment compared with the control fragment allowed for quantification of the extent of depurination (Parikh et al 2002(Parikh et al , 2005Baykal and Tumer 2007;Li et al 2007;Chiou et al 2008). Other methods to measure depurination include quantification of the adenine released from RIP depurination by HPLC, a calorimetric assay (Brigotti et al 1998;Heisler et al 2002) or an enzymatically coupled assay to continuously measure the release of adenine by RIPs (Sturm and Schramm 2009).…”
Section: Introductionmentioning
confidence: 99%